COMPACT STARS : NUCLEAR PHYSIS, PARTICLE PHYSICS AND GENERAL RELATIVITY - Tamta, Ritu, contributor; Fuloria, Pratibha, contributor; Ding, Guoqiang, contributor; Huang, Chunping, contributor; Qu, Jinlu, contributor; Sashikanth, R., contributor; Maurya, S. K., contributor; Gupta, Y. K., contributor; Ray, Saibal, contributor; Deb, Debabrata, contributor; Takisa, P. Mafa, contributor; Maharaj, S. D., contributor; et al. (London, UK : Auris Reference, 2018)
Includes bibliographical references and index